2000
DOI: 10.1046/j.1523-1747.2000.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

A Th2 Chemokine, TARC, Produced by Keratinocytes May Recruit CLA+CCR4+ Lymphocytes into Lesional Atopic Dermatitis Skin

Abstract: Atopic dermatitis is an inflammatory skin disease in which the inflammation is characterized by the influx of lymphocytes into the dermis. It is generally believed that atopic dermatitis is a Th2-type disease, i.e., the T lymphocytes produce interleukin-4, interleukin-5, interleukin-10, and interleukin-13, although it has become evident in recent years that the cytokine profile in the skin changes during the course of the disease towards a Th1-Th2 mixed cytokine profile (interferon-gamma, tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
247
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(266 citation statements)
references
References 47 publications
12
247
3
4
Order By: Relevance
“…These results contrast somewhat with Vestergaard et al (17) who concluded that CCL17/TARC was not in normal skin, but was expressed by keratinocytes but not endothelial cells in AD patients. Because both CCL27 and CCL17/TARC protein are present on inflamed cutaneous endothelium, trigger rapid adhesion of CLA ϩ memory T cells, and stimulate CLA ϩ memory T cell migration, CCR4 and CCR10 may provide redundant mechanisms to allow CLA ϩ /CCR4 ϩ /CCR10 ϩ memory T cell entry into inflamed cutaneous sites.…”
Section: Discussioncontrasting
confidence: 96%
“…These results contrast somewhat with Vestergaard et al (17) who concluded that CCL17/TARC was not in normal skin, but was expressed by keratinocytes but not endothelial cells in AD patients. Because both CCL27 and CCL17/TARC protein are present on inflamed cutaneous endothelium, trigger rapid adhesion of CLA ϩ memory T cells, and stimulate CLA ϩ memory T cell migration, CCR4 and CCR10 may provide redundant mechanisms to allow CLA ϩ /CCR4 ϩ /CCR10 ϩ memory T cell entry into inflamed cutaneous sites.…”
Section: Discussioncontrasting
confidence: 96%
“…After polarization into Th2 cells, CD4 + T cells express the chemokine receptors CCR3, CCR4 and CCR8, while Th1 cells preferentially express CXCR3 and CCR5 [14,15]. The CCR4 ligand TARC/ CCL17 has been shown to be strongly chemotactic for Th2 cells [6] and CLA + CD4 + T cells of the memory/ effector subtype [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…TARC/CCL17-mediated recruitment of Th2 cells and CLA + CD4 + T cells was shown to play a major role in allergic diseases like atopic dermatitis [16,17], allergic asthma [18][19][20], allergic rhinitis [21] and allergic contact dermatitis [22].…”
Section: Introductionmentioning
confidence: 99%
“…These CCR4 + cells also express the cutaneous lymphocyte antigen (CLA), a ligand for E-selectin [12,17,18]. This suggests that T cell homing to inflamed skin is governed by tissue-specific interactions mediated by CLA and CCR4 on T cells interacting with E-selectin and CCL17 on endothelium [19,20]. CCR10 binding to CCL27 can also mediate T cell migration to dermal inflammation.…”
Section: Introductionmentioning
confidence: 99%